THE RELATIONSHIP BETWEEN THE LEVEL OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) AND THE INTENSITY OF DIGITAL PUBLIC COMMUNICATION ON PLN'S CORPORATE IMAGE AMONG FOLLOWERS OF THE @PLN_ID INSTAGRAM ACCOUNT - Raden Ayu Annisa Maharani Wulandari; Indriati Yulistiani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
In the era of digital transformation, PT PLN (Persero) faces challenges in maintaining its corporate image due to the increasing number of service-related complaints in cyberspace. This study aims to analyse the relationship between Customer Relationship Management (CRM) and digital public communication on the corporate image among followers of the @pln_id Instagram account. The study employed an explanatory quantitative methodology with a positivist approach. The research sample consisted of 100 respondents who were active followers of the @pln_id Instagram account and were selected using a purposive sampling technique. The theoretical framework was based on Customer Relationship Management proposed by Payne and Frow (2005) and Two-Way Symmetrical Communication developed by Grunig and Hunt (1984). Data were analysed using instrument testing, classical assumption testing, and simple linear regression analysis. The findings indicate that Customer Relationship Management (CRM) has a positive and significant relationship with corporate image. Digital public communication also demonstrates a positive and significant relationship with corporate image. This study recommends that the Public Relations division of PT PLN (Persero) optimise the dimensions of customer satisfaction and customer trust within its Customer Relationship Management (CRM) practices, while also enhancing message credibility in digital public communication to strengthen the company's corporate image and reduce negative sentiment on social media.